Antihyperglycemic Activity of TLC Isolates from the Leaves of Aloe megalacantha Baker in Streptozotocin-Induced Diabetic Mice - Araya, Tsgabu Yohannes (Diabetes Metab Syndr Obes, 2021)
BACKGROUND: Diabetes mellitus (DM) is a group of metabolic disorders that are characterized by hyperglycemia which results from defects in insulin release or its efficient use by the human body. Although significant progress has been made to manage DM and related complications, it remains a major global health problem. To this end, the search for new antidiabetic drugs from traditionally claimed medicinal plants is important. Aloe megalacantha Baker is an endemic plant used traditionally to treat diabetes in Ethiopia. This study aimed to investigate antidiabetic activity of isolates from the leaf of A. megalacantha Baker in streptozotocin-induced diabetic mice. METHODS: The exudate of A. megalacantha was collected by cutting the leaves and scraping the yellow sap and then dried at room temperature. The dried exudate was subjected to repeated thin layer chromatographic (TLC) separations using a mixture of solvent system to isolate the major compounds identified on the TLC plate. A single dose of streptozotocin (50 mg/kg) was injected intraperitoneally to overnight fasted mice to induce diabetes. Antidiabetic activity of TLC isolates was assessed by in vivo methods including oral glucose tolerance test, antihyperglycemic and hypoglycemic activity tests. RESULTS: Three major isolates were obtained from the TLC analysis of the exudate of A. megalacantha. Exudate and TLC isolates were found to be non-toxic up to a dose of 2000 mg/kg. The TLC isolates (Ia and Ib) significantly (p<0.05) reduced blood glucose levels and also increased body weight change of the diabetic mice compared with control groups. CONCLUSION: The present study demonstrated the ability of the exudate of A. megalacantha and its TLC isolates to significantly decrease blood glucose levels and increase body weights in mice, thus strengthening the claim of its traditional use in DM-related disorders.